Transition from image intensifier to flat panel detector in interventional cardiology: Impact of radiation dose - Livingstone, Roshan S. (J Med Phys, 2015)
Flat panel detector (FPD) technology in interventional cardiology is on the increase due to its varied advantages compared to the conventional image intensifier (II) systems. It is not clear whether FPD imparts lower radiation doses compared to II systems though a few studies support this finding. This study intends to compare radiation doses from II and FPD systems for coronaryangiography (CAG) and Percutaneous Transluminal Coronary Angioplasty (PTCA) performed in a tertiary referral center. Radiation doses were measured using dose area product (DAP) meter from patients who underwent CAG (n = 222) and PTCA (n = 75) performed using FPD angiography system. The DAP values from FPD were compared with earlier reported data using II systems from the same referral center where the study was conducted. The mean DAP values from FPD system for CAG and PTCA were 24.35 and 63.64 Gycm(2) and those from II system were 27.71 and 65.44 Gycm(2). Transition from II to FPD system requires stringent dose optimization strategies right from the initial period of installation.